Internalization and degradation of macrophage Fc receptors bound to polyvalent immune complexes (The Rockefeller University Press, 1984)
We have studied the Fc receptor-mediated pinocytosis of immunoglobulin G (IgG)-containing immune complexes by mouse macrophages. IgG complexes were formed from affinity-purified rabbit dinitrophenyl IgG and dinitrophenyl modified BSA at molar ratios of 2.5-10:1. Both the specificity of binding and the fate of internalized receptors were analyzed using monoclonal and polyclonal anti-Fc receptor antibodies. Based on the susceptibility of surface-bound ligand to release by proteolysis, we have found that at 37 degrees C, 125I-labeled IgG complexes were rapidly internalized (t1/2 less than 2 min) and delivered to lysosomes; acid-soluble 125I was detectable in the growth medium within 5-10 min of uptake. However, kinetic evidence indicated that Fc receptors were not efficiently re-used for multiple rounds of ligand uptake. Instead, macrophages that were exposed continuously to saturating concentrations of IgG complexes exhibited a selective and largely irreversible removal of Fc receptors from the plasma membrane. This loss of surface receptors correlated with an increased rate of receptor turnover, determined by immune precipitation of Fc receptors from 125I-labeled macrophages. Thus, in contrast to the results obtained in the accompanying paper (I. Mellman, H. Plutner, and P. Ukkonen, 1984, J. Cell Biol. 98:1163-1169) using a monovalent ligand, these data indicate that the interaction of Fc receptors with polyvalent complexes leads to the degradation of both ligand and receptor following their delivery to lysosomes.